KOMPETENSI PROFESIONAL DALAM MENINGKATKAN KINERJA GURU PAUD KELOMPOK BERMAIN MEKAR TUNJUNG LANDIH BANGLI - Putri Anugrah, Ketut Yosi; Rianita, Ni Made (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the professional competence of teachers in improving performance at PAUD Kelompok Bermain Mekar Tunjung Landih Bangli. The research employs a descriptive qualitative approach using purposive sampling involving three key informants: the principal and two active teachers. Data were collected through observation, semi-structured interviews, and documentation. The data analysis technique follows Miles and Huberman's model, which includes data reduction, data display, and conclusion drawing/verification. The results show that teachers demonstrate adequate professional competence in lesson planning, subject mastery, and implementing play-based learning activities. However, challenges persist, such as limited access to formal training, technological constraints, and dual domestic roles. The institution has responded with internal training, learning communities, and external collaborations. A supportive work environment and strong intrinsic motivation are identified as key factors in sustaining teacher performance. Therefore, continuous development of professional competence is essential to ensure the quality of early childhood education services.